Ідея соборності в українському часописі Буковини «Каменярі» (1909-1914, 1921-1922) - Попович, Юлія Олександрівна (Інститут журналістики КНУ імені Тараса Шевченка, 2015)
The article aims at investigating the way the idea of Ukraine unification was reflected in the newspaper «Kameniari». One of the main results of the research is that in difficult socio-political conditions of Bukovyna, when it was under the Austro-Hungarian Empire and a part of the royal Romania, «Kameniari» embodied in life their program, conducted a kind of preparatory work so that in the future Bukovyna might become a part of one big country – Ukraine. Many published materials worked for the national idea. During eight years of their life «Kameniari» united the Ukrainians by their publications, namely, provided information about social life all over Ukrainian lands with a focus on Kyiv as the center of Ukrainian statehood; the newspaper published works of outstanding authors from Ukraine, strengthened and gave life to Bukovynian ukrainians spiritually – through the publication of materials on Shevchenko topic. «Kameniari» united Bukovynian people with Naddnipryanshchyna with the help of informational, cultural, and artistic articles about prominent figures of Ukrainian culture. The newspaper popularized the unificational ideas of writers from Bukovyna; editorial continuously informed about new books, periodicals in Kiev
The idea of unification in the Bukovynian ukrainian newspaper «Kameniari» (1909–1914; 1921–1922)
Keywords: соборність, періодика, часопис «Каменярі», преса Буковини; unification, periodicals, newspaper «Kameniari», the press of Bukovyna